A fatigue damage and residual strength model for unidirectional carbon/epoxy composites under on-axis tension-tension loadings. (October 2017) - Llobet, J.; Maimí, P.; Mayugo, J.A.; Essa, Y.; Martin de la Escalera, F.
Highlights: The proposed model requires only the characterization of stiffness loss. The ultimate strain remains constant after fatigue damage. The residual stiffness evolves in the same manner as the strength. The proposed model predicts fatigue life reasonably well. Abstract: Fibre-reinforced composites experience a degradation of stiffness and strength during fatigue life. Understanding the reduction of these properties is fundamental to establish a reliable fatigue life prediction methodology. This work investigates the loss of stiffness and strength in advanced unidirectional carbon/epoxy laminates under on-axis tension-tension loads. A phenomenological stiffness-based fatigue model is formulated within the framework of continuum damage mechanics, where damage is described by the reduction of the in-plane longitudinal stiffness. The particularity of the model is to assume that the ultimate strain remains constant after fatigue damage. Thus, the residual strength model and the S-N curves are deduced from the residual stiffness model. This assumption reduces the experimental characterization of phenomenological-based approaches. The experimental challenges found in the fatigue experiments are also discussed. The accuracy of the model is verified by comparing the experimental data with the derived S-N curves.